Implementasi Model Kooperatif Tipe TGT dalam Pembelajaran IPS Tema Keberagaman Suku Bangsa di Indonesia di SDN Cijengkol 01 - Putri, Nursoleha Mumpuni; Susilawati, Susilawati; Ridwan, Ita Rustiati (Didaktika, 2021)
The problem of understanding students' concepts on social sciences that are still established criteria became the background of this study. This was evidenced from the preliminary notes that 10% of students reach a minimum score of ≥ 75. This research used the Team Game Tournament type of cooperative learning, which is part of the type or model of cooperative learning that is very flexible to use to invite all students to activities without status support and include roles students `to make a tutor and in it is a game or game and reinforcement. Fun learning process activities can make students interested in this learning. This is due to the age of elementary school students whose nature still likes to play and tends to allow exciting learning. Learning must also be concrete in nature. It is easier for students to accept the material presented by the teacher during the research learning process which took place at SDN Cijengkol 01 for fourth-grade students of even semesters with 46 students. This research aimed to improve the learning ability of students and increasing activities in the learning process. Therefore, this learning model is needed. The type of research used was Classroom Action Research. The instruments used were test and observation sheets. This research was conducted in two cycles. The acquisition of the classical average value of the first cycle 64. The percentage of learning completeness is 30%. The second rank is the acquisition of an average value of 86 presentations of classical learning completeness as much as 91.34% of the research was declared successful because it has reached the predetermined standard of completeness. This learning model can improve learning abilities and improve student learning outcomes.